Measurement of human capabilities - Paul Anand; Graham Hunter; Ian Carter; Keith Dowding; Francesco Guala (The Open University, Economics Department, 2007)
The paper is motivated by sustained interest in the capabilities approach to welfare economics combined with the purported paucity of economic statistics that measure capabilities at the individual level. Specifically, it takes a focal account of normatively desirable capabilities constitutive of a good life and operationalizes that account by means of a new survey instrument used to elicit information about capabilities at the individual level. The paper explores the extent to which these capabilities are co-variates of a life satisfaction measure of utility (happiness) and finds that many are. Aspects of robustness are explored using standard socio-demographic variables as well as a relatively novel control for personality; in addition, a range of different models are explored and sub-population differences are examined.
Keywords: D60; C80; 330; capabilities; indicators; measurement; human development; welfare; happiness; life satisfaction; controls; personality; Soziale Gerechtigkeit; Zufriedenheit; Sozialer Indikator; Wohlfahrtstheorie